Pengaruh Citra Merek dan Kualitas Produk Terhadap Loyalitas Pelanggan J.Co Donuts & Coffee di Palembang - Luki Ardinata; Destia Aktarina (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2019)
The formulation of the problems discussed in this study are: Are there effects of brand image and product quality both simultaneously and partially on the loyalty of J.Co Donuts customers. The objectives and benefits in this study are: To find out whether there are simultaneous effects of brand image and product quality and impartially on J.Co Donuts customer loyalty. The analytical method used is Multiple Linear Regression. Simultaneous test results (F test) obtained F count of 50,501 with a significance level of 0,000, obtained for F table of 3,195 (see attachment F Table Statistics). So it can be concluded that F count > F table (50,501 > 3,195) so the null hypothesis is rejected. It can be concluded that the Brand Image variable (X1) and Product Quality (X2) together influence the Purchase Decision (Y). Partial test results (t test) can be explained: Brand Image Variables (X1) have a significant effect on Purchase Decisions (Y) results obtained t count of 3.666 with a significant value of 0.001, the value of t count > t table (3.666> 1.678), be a hypothesis alternative is accepted and the null hypothesis is rejected that Brand Image (X1) has a significant effect on Purchase Decision (Y). The coefficient of determination R2 obtained is 0.682 (68.2%) means that the Brand Image variable (X1), Product Quality (X2) describes Customer Loyalty (Y) by 68.2% while the remaining 31.8% (100% - 68, 2%) can be explained by other variables such as price, service quality, emotional factor, cost and the ease of getting a product that is not examined in this study which is seen in Adjusted R Square.